Interfacial double layer mediated electrochemical growth of thin-walled platinum nanotubes. (14th December 2016) - Zhang, Liqiu; Kim, Sang Min; Cho, Sanghyun; Jang, Hee-Jeong; Liu, Lichun; Park, Sungho
Abstract: This work demonstrates that thin-walled platinum nanotubes can be readily synthesized by controlling the interfacial double layer in alumina nanochannels. The gradient distribution of ions in nanochannels enables the creation of Pt nanotubes with walls as thin as 5 nm at the top end when using a solution containing polyvinylpyrrolidone (PVP) and chloroplatinic acid (H2 PtCl6 ) under the influence of an electric potential in nanochannels. The highly efficient formation of thin-walled Pt nanotubes is a result of the concentration gradient of PtCl 6 2 − and a thick double layer, which was caused by the low concentration of Pt precursors and the enhanced surface charge density induced by protonated PVP steric adsorption. This well-controlled synthesis reveals that the interfacial double layer is a useful tool to tailor the structure of nanomaterials in a nanoscale space, and holds promise in the construction of more complex functional nanostructures.